AGE AND INFECTION: A COMPREHENSIVE STUDY OF SYNERGISTIC GANGRENE - Khurram Niaz; Akhtar, Muhammad Saeed; Darakshan Sehr Masood; Muhammad Nauman Ashraf; Fawad Hameed; Muhammad Ahsan Mustafa (Pakistan Armed Forces Medical Journal, 2025)
Objective: To analyze and interpret the impact of age on the etiology of synergistic gangrene, identifying key age-related risk factors, bacterial profiles, clinical presentations, and treatment outcomesStudy Design: A Retrospective Cross-sectional Study Design.Place and duration of study: Department of Surgery, CMH BWP, and SZH RYK from August 2019 to August 2023.Patients and Methods: 300 patients with clinical suspicion of synergistic gangrene were included. Data was collected for demographic details, clinical information, laboratory findings, and treatment modalities. The study population was divided into three age groups: 18-30 years, 31-60 years, and over 60 years.Results: Younger adults (18-30 years) presented with aggressive symptoms affecting limbs, while middle-aged patients (31-60 years) showed moderate severity involving the abdomen. The elderly (over 60 years) displayed severe symptoms primarily affecting genital areas. On cultures, Streptococcus pyogenes was more prevalent in the youngest group, and Clostridium perfringens and Escherichia coli in the middle-aged group. Methicillin-resistant Staphylococcus aureus (MRSA) showed consistent prevalence across all age groups. Immune responses are correlated with age, demonstrating distinct white blood cell counts, C-reactive protein levels, antibiotic responses, and surgical interventions.Conclusion: This comprehensive study underscores the significance of age in influencing synergistic gangrene's clinical acumen, pathogens, Host responses, and Treatment approaches. The findings emphasize the importance of considering age-related factors in diagnosis and management strategies, paving the way for improved personalized care and appropriate interventions for this life-threatening infection.Keywords: synergistic gangrene, necrotizing fasciitis, age, bacterial isolates, clinical presentation, treatment outcomes, immune response, personalized care.